2019
DOI: 10.1111/1748-8583.12251
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of LGBT‐friendly practices: The effect of institutional pressures and strategic choice

Abstract: This study explores contextual and organisational factors that influence the likelihood of adopting lesbian, gay, bisexual, and transgender (LGBT)-friendly practices. Drawing on institutional theory, we hypothesise that state laws, state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 107 publications
3
34
0
Order By: Relevance
“…This line of argumentation is also broadly consistent with the institutional and legitimacy theories used in the CSR literature in tandem with the stakeholder theory (see, e.g., Fernando and Lawrence, 2014). These theories suggest that CSR initiatives such as those related to LGBT-friendly policies can be induced by the firms' pursuit to build reputation and achieve legitimacy in the context of their social environment (e.g., Roumpi et al, 2020). Given that perceived LGBT friendliness is to a large extent conjoined with inclusive and non-discriminatory employee policies and 3 An extensive literature has been devoted to examining the relation between CSR and firm performance (for reviews, see, e.g., Griffin and Mahon, 1997;Orlitzky, 2001;Orlitzky et al, 2003;van Beurden and G össling, 2008;Peloza, 2009;Aguinis and Glavas, 2012;Huang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This line of argumentation is also broadly consistent with the institutional and legitimacy theories used in the CSR literature in tandem with the stakeholder theory (see, e.g., Fernando and Lawrence, 2014). These theories suggest that CSR initiatives such as those related to LGBT-friendly policies can be induced by the firms' pursuit to build reputation and achieve legitimacy in the context of their social environment (e.g., Roumpi et al, 2020). Given that perceived LGBT friendliness is to a large extent conjoined with inclusive and non-discriminatory employee policies and 3 An extensive literature has been devoted to examining the relation between CSR and firm performance (for reviews, see, e.g., Griffin and Mahon, 1997;Orlitzky, 2001;Orlitzky et al, 2003;van Beurden and G össling, 2008;Peloza, 2009;Aguinis and Glavas, 2012;Huang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On these grounds and acknowledging the variability in the adoption and nature of workfamily policies across organizations (Ingram and Simons, 1995;Mullins and Holmes, 2018;Osterman, 1995;Roumpi et al, 2020), the objective of this paper is to shed light on the sources of this variation in terms of both provision and inclusiveness. Recognizing the crucial role of top management in the recognition and formation of responses to work-family issues (Milliken et al, 1998;Mullins and Holmes, 2018) and drawing on the upper echelons' (UE) perspective (Hambrick, 2007;Hambrick and Mason, 1984), the described variation is proposed to be, at least partially, attributable to the differences in cheif executive officers' (CEOs) values and beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…CEOs have adequate levels of authority and power to steer the vision and moral obligations of organizations (Gilbert and Ivancevich, 2000). In concert with recent studies that have shown that CEOs' political ideology is related to organizations' adoption of LGBT-friendly practices (Roumpi et al, 2020) and CSR (Gupta et al, 2019), political ideology is conceptualized as an overarching construct that encapsulates the CEOs' values and beliefs that drive their decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This line of argumentation is also broadly consistent with the institutional and legitimacy theories used in the CSR literature in tandem with the stakeholder theory (see, e.g., Fernando and Lawrence, 2014). These theories suggest that CSR initiatives such as those related to LGBT-friendly policies can be induced by the firms' pursuit to build reputation and achieve legitimacy in the context of their social environment (e.g., Roumpi et al, 2020). Given that perceived LGBT friendliness is to a large extent conjoined with inclusive and non-discriminatory employee policies and 3 An extensive literature has been devoted to examining the relation between CSR and firm performance (for reviews, see, e.g., Griffin and Mahon, 1997;Orlitzky, 2001;Orlitzky et al, 2003;van Beurden and Gössling, 2008;Peloza, 2009;Aguinis and Glavas, 2012;Huang, 2021).…”
Section: Introductionmentioning
confidence: 99%